2006
DOI: 10.1103/physrevlett.97.060401
|View full text |Cite
|
Sign up to set email alerts
|

Self-Localization of Bose-Einstein Condensates in Optical Lattices via Boundary Dissipation

Abstract: We introduce a technique to obtain localization of Bose-Einstein condensates in optical lattices via boundary dissipations. Stationary and traveling localized states are generated by removing atoms at the optical lattice ends. Clear regimes of stretched-exponential decay for the number of atoms trapped in the lattice are identified. The phenomenon is universal and can also be observed in arrays of optical waveguides with mirrors at the system boundaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
139
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(145 citation statements)
references
References 26 publications
5
139
0
1
Order By: Relevance
“…Indeed, their ability to pump energy from neighboring sites is a distinctive signature of DB self-excitation [32], e.g. observed as a consequence of surface cooling [33][34][35][36] or due to modulational instability of band-edge waves in nonlinear lattices [37,38]. Furthermore, within the frame of a nonlinear network model, we have shown that highly energetic DBs can form easily in proteins [33], and that they feature strongly site-modulated properties [39].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, their ability to pump energy from neighboring sites is a distinctive signature of DB self-excitation [32], e.g. observed as a consequence of surface cooling [33][34][35][36] or due to modulational instability of band-edge waves in nonlinear lattices [37,38]. Furthermore, within the frame of a nonlinear network model, we have shown that highly energetic DBs can form easily in proteins [33], and that they feature strongly site-modulated properties [39].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we found that in the presence of the decay rate imbalance between the coupled disks, there exists an anomalous relaxation behavior similar to the one discussed in Ref. [27][28][29][30][31]. This result identifies the system of coupled optical resonators as a convenient platform for experimental study of this phenomenon, which so far, has eluded experimental observation.…”
Section: Discussionmentioning
confidence: 69%
“…and demonstrate anomalously slow relaxation dynamics [27] (due to boundary losses) similar to the one appeared in glass materials. This relaxation dynamics has generated recently a great deal of theoretical interest in the context of cold atoms [28][29][30][31] and coupled cavities [17,18]. At the same time, while self-trapping in systems with conserving number of particles or energy has been observed experimentally [24], it is still yet to be observed in in any physical realization of the DNLSE with losses.…”
Section: Introductionmentioning
confidence: 99%
“…The discrete breathers which are observed experimentally in coupled antiferromagnetic layers [16][17][18] can also be considered as being excited in the relaxation processes. Inspired by these findings, boundary dissipation was also used in optic lattices to make the formation of the long-lived discrete breather and consequently leading to the localization of Bose-Einstein condensates [65][66][67][68][69][70] . It is numerically revealed that the initial average energy per site of the thermalized lattice must higher than a critical energy to excite the long-lived discrete breather in both one dimensional nonlinear lattices 51,52 and two dimensional nonlinear lattices 49,53,54 with boundary dissipation.…”
Section: Introductionmentioning
confidence: 99%